A educação ambiental presente nos programas de uso público em parques estaduais localizados no município de São Paulo - Wick, Maíra Arantes Leite [UNESP] (2014)
This research investigates the educational processes that occur in Conservation Units. To undertake the protected areas selection, we have delimited only those located in city of São Paulo, due to the geographical location and proximity to each other, which would ensure the educational activities monitoring. From this context we developed the following research question – which environmental education processes has been implemented in protected areas? Important to emphasize that given the fact that some research indicates low theoreticalpractical questioning in the Brazil's environmental education proposals, this research's mail goal is to understand which elements constitute and guide the development of environmental education activities currently implemented in Conservation Units, especially on the Jaraguá State Park, the Cantareira State Park and the Serra do Mar State Park. We also seek to consider the influence that the historical process of environmental education's formalization exerts in these areas. From the elaborate research question, we consider that this is a research with qualitative character. The data collection procedures used were: search for the Management plans of the three selected parks, conducting systematic observations about the developed environmental education practices and semi-structured interviews with Park's actors responsible for planning and implementing the environmental education activities. The gathered information were systematized and analyzed based on guidelines from the perspective of Content Analysis. Our analysis indicate that the Parks undertake environmental education initiatives that seek to promote the recognition and enhancement of Conservation Units as places that play an important role in ensuring nature's protection. The state parks have protection, research and public use as pillars of performance. Environmental education is considered, therefore, a fulcrum to achieve the proposed...